Rheological properties of crosslinked unentangled and entangled Poly(methyl acrylate) nanocomposite networks. (22nd August 2022) - Feng, Yi; Wu, Di; Li, Ruhao; Akcora, Pinar
Abstract: This work is designed to explore the effect of entanglements and particle loading on viscoelastic properties of crosslinked polymer nanocomposites. The entangled and unentangled poly(methyl acrylate) composite networks were synthesized and characterized in linear rheology. We found that the elastic moduli and crosslinking degree of entangled composite networks were unaffected with particle loading. For the unentangled composite networks, both elastic moduli and crosslinking degree enhanced with particle loading. The reinforcement factor analyzed with the recovery of modulus after large deformation indicated that entangled composite networks fully recovered their initial moduli, suggesting the high entanglements can sustain large deformation and maintain their initial chain conformation even at high particle loadings. The unentangled networks did not recover their initial storage moduli after large deformation, posing the non-deformability of the highly crosslinked networks. Graphical abstract: Image 1 Highlights: Entangled polymer crosslinking in nanocomposites for enhanced reinforcement is reported. Particles can enhance crosslinking degree in unentangled (permanent) polymer networks. Entangled composite networks can fully recover their initial moduli after nonlinear deformation. The first comparison of unentangled and entangled composite networks.